2008
DOI: 10.1111/j.1349-7006.2008.00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of epidermal growth factor receptor (EGFR) gene mutations with EGFR amplification in advanced non‐small cell lung cancer

Abstract: Somatic mutations in the epidermal growth factor receptor (EGFR) gene are associated with the response to EGFR tyrosine kinase inhibitors in patients with non-small cell lung cancer (NSCLC). Increased EGFR copy number has also been associated with sensitivity to these drugs. However, given that it is often difficult to obtain sufficient amounts of tumor tissue for genetic analysis from patients with advanced NSCLC, the relationship between these two types of EGFR alterations has remained unclear. We have now e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 42 publications
(93 reference statements)
1
19
0
Order By: Relevance
“…Subsequent mutation analyses of B-RAF or EML4-ALK translocations will further reduce the percentage of cases with unreliable results, since these alterations are currently considered to be mutually exclusive with EGFR mutations [16]. Furthermore, ARMS or yet other experimental methods [17][18][19][20][21][22] with a putative higher sensitivity for the detection of EGFR mutations than Sanger sequencing may be used subsequently in such settings.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequent mutation analyses of B-RAF or EML4-ALK translocations will further reduce the percentage of cases with unreliable results, since these alterations are currently considered to be mutually exclusive with EGFR mutations [16]. Furthermore, ARMS or yet other experimental methods [17][18][19][20][21][22] with a putative higher sensitivity for the detection of EGFR mutations than Sanger sequencing may be used subsequently in such settings.…”
Section: Discussionmentioning
confidence: 95%
“…Multiple studies have established that EGFR mutations are more common in women than men, in patients who have never smoked tobacco than in patients who have smoked tobacco, and in East Asians than in other ethnic groups. 7,2529 In contrast to EGFR -mutated lung cancer, ALK gene fusions do not show sharp differences in prevalence according to sex and ethnic origin, but do show a similar strong association with patients who have never smoked tobacco and younger age. 11,18,30,31 However, while these clinical characteristics may have value for population studies, they are insufficiently specific to be used to select individual patients for treatment with a targeted inhibitor.…”
Section: Section I: When Should Molecular Testing For Nsclc Be Performentioning
confidence: 98%
“…Recent studies have reported that EGFR mutations occur early during multistage pathogenesis of NSCLC and precede amplification, but not necessarily high polysomy [37,40,41]. In addition, Morinaga et al (2008) observed a specific association between mutations and amplification, underlying that EGFR amplification, but not high polysomy, correlates with mutations [42]. …”
Section: Discussionmentioning
confidence: 99%